Morphological and Molecular Characterization of Rhizoctonia solani Isolates from Two Different Rice Varieties - Aisyah Surya Bintang; Arif Wibowo; Achmadi Priyatmojo; Siti Subandiyah (Jurnal Perlindungan Tanaman Indonesia, 2017)
Six isolates of Rhizoctonia solani, i.e. two isolates collected from infected rice plants and four isolates from laboratory collection were studied by using morphological characters and molecular analysis. Un-weighted pair group method with arithmetic mean dendogram constructed based on cluster analysis showed that these isolates were grouped into three clusters at the 0.77 similarity coefficient. Cluster I consisted of BA, BNJ, and NBR isolates with 100% similarity and indicated that those were from AG 1 IA sub group, cluster II consisted of BND, and cluster III consisted of SL1 and SL2. Mycelium was very light brown or whitish with few and moderate sclerotia except SL1 and SL2. Molecular characterization showed that BA, BNJ, and NBR were amplified at 140 bp using Rs1F/Rs2R specific primer for R. solani AG1 IA. All isolates were amplified between 350−400 bp using Rhsp1 primer, meanwhile SL1 and SL2 were not amplified using AG2sp and AG22sp2 primers. Based on Maximum Likelihood tree analysis showed that SL1 and SL2 had high similarity based on ITS sequence data.IntisariEnam isolat Rhizoctonia solani yang berasal dari tanaman padi bergejala dan koleksi laboratorium diuji secara morfologi dan molekuler. Analisis UPGMA dengan koefisien persamaan 0,77 menunjukkan bahwa enam isolat tersebut terbagi atas tiga klaster. Klaster I terdiri atas isolat BA, BNJ, dan NBR dengan kesamaan 100% dan menunjukkan bahwa isolat tersebut berasal dari subgrup AG 1 IA , klaster II yakni isolat BND, dan klaster III terdiri atas isolat SL1 dan SL2. Miselium berwarna putih hingga cokelat muda dengan jumlah sklerotia sedang, kecuali isolat SL1 dan SL2. Uji keragaman secara molekuler menunjukkan bahwa isolat BA, BNJ, dan NBR teramplifikasi pada kisaran 140 bp dengan menggunakan  primer Rs1F/Rs2R yang merupakan primer spesifik dari R. solani AG1 IA. Seluruh isolat teramplifikasi pada kisaran 350−400 bp dengan menggunakan primer Rhsp1, sedangkan isolat SL1 dan SL2 keduanya tidak teramplifikasi oleh primer AG2sp dan AG22sp2. Analisis Maximum Likelihood tree berdasar data sekuen ITS menunjukkan bahwa isolat SL1 dan SL2 memiliki tingkat kesamaan yang tinggi.